Water channels and barriers formed by claudins. Issue 1 (June 2017) - Rosenthal, Rita; Günzel, Dorothee; Theune, Dian; Czichos, Carolina; Schulzke, Jörg‐Dieter; Fromm, Michael
Abstract : Physiological studies in leaky epithelia, like kidney proximal tubules and the small intestine, have documented water transport via both transcellular and paracellular pathways. The discovery of aquaporin water channels provided a molecular basis for transcellular water movement. In contrast, the contribution, or even existence, of a specific paracellular water pathway has been disputed for a long time, until the cation channel–forming tight junction protein claudin‐2 was shown to also permit the paracellular passage of water through its pore. In proximal kidney tubules, claudin‐2–based water transport contributes 23–30% of the total water transport. Other paracellular ion channels (claudin‐10a, ‐10b, and ‐17) proved to be impermeable to water, although their pore size would be sufficient for water molecules to pass. Studies of barrier‐forming claudins, like claudin‐1 and claudin‐3, which tighten the paracellular pathway against ions and larger solutes, indicate that changes in the expression of these sealing claudins do not influence transepithelial water permeability. The present genetic, molecular, computational, and physiological studies are just now beginning to probe the mechanisms and regulation of paracellular permeation.